1992
DOI: 10.1111/j.1348-0421.1992.tb02099.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Peptidoglycans in Campylobacter Species

Abstract: Peptidoglycans (PG) from Campylobacter coli, Campylobacter jejuni, and Campylobacter fetus were composed of muramic acid, glucosamine, alanine, glutamic acid, and diaminopimelic acid in a molar ratio of 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Only one very minor peak with a pentapeptide side chain was detected in C. jejuni , a TetraPenta dimer with a Gly residue at position 5, as opposed to the more common D-Ala. Muropeptides with 3-3 crosslinks or Lys-Arg residues indicating bound lipoprotein were not detected and thus are either not present or present in very small amounts. The degree of cross-linking at 29.5% is consistent with the value of 30% published previously [17]. The average glycan chain length determined by the fraction of 1,6-anhydromuramic acid containing muropeptides from chain ends was 14.7 dissacharide units.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Only one very minor peak with a pentapeptide side chain was detected in C. jejuni , a TetraPenta dimer with a Gly residue at position 5, as opposed to the more common D-Ala. Muropeptides with 3-3 crosslinks or Lys-Arg residues indicating bound lipoprotein were not detected and thus are either not present or present in very small amounts. The degree of cross-linking at 29.5% is consistent with the value of 30% published previously [17]. The average glycan chain length determined by the fraction of 1,6-anhydromuramic acid containing muropeptides from chain ends was 14.7 dissacharide units.…”
Section: Resultssupporting
confidence: 90%
“…Campylobacter PG contains meso -diaminopimelic acid ( meso -Dap) in its peptide side chains and is modified by O-acetylation [17], [18], but the detailed muropeptide composition had not previously been elucidated. Bioinformatic analyses identified 3 putative PG synthases in C. jejuni : the penicillin-binding proteins (PBPs) PBP1A (cjj81176_0536), PBP (cjj81176_0550), and PBP2 (cjj81176_0680), but there are no predicted homologs of low-molecular weight PBPs such as DD-endo- or carboxypeptidases.…”
Section: Introductionmentioning
confidence: 99%
“…The concomitant shift in the morphology of the cells back to being predominantly spiral would suggest that the formation of coccal cells previously was indicative only of injury and cell degeneration. This was substantiated by the ultrastructural features of the coccal cells which showed membrane degradation and cytoplasmic leakage, similar to that reported previously for coccal cells derived from batch and plate cultures (Buck et al 1983;Ng et al 1985;Moran and Upton 1987b;Jones et al 1991;Amano and Shibata 1992;Jacob et al 1993).…”
Section: Discussionsupporting
confidence: 88%
“…Studies using chemical indicators of 'viability' have demonstrated that 'stressed' non-culturable cells still retain respiratory activity (Rollins and Colwell 1986;Beumer et al 1992;Medema et al 1992;Boucher et al 1994;Fearnley et al 1996). By contrast, other indicators of viability, such as intracellular and extracellular ATP levels and cellular ultrastructure, suggest that the cells are degenerate (Buck et al 1983;Upton 1986, 1987b;Amano and Shibata 1992;Boucher et al 1994). Experiments on the infectivity of non-culturable forms of Camp.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the yield of PG extracted from CF cells of C. coli, C. jejuni and C. fetus was much lower than that from RF cells. [75]. Remarkably, PG was always obtainable from C. fetus, coincident with inability of this subspecies to form CF.…”
Section: Factors Involved In Bacterial Cell Shape Maintenancementioning
confidence: 95%